Application Of Criminal Sanctions Against Corporations For Human Trafficking In Indonesia - Muhammad Safar; T. Riza Zarzani; Ismaidar Ismaidar (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2024)
In recent years, news about human trafficking both domestically and across countries has increasingly been broadcast in print and electronic media. The rise in crimes that occur is caused by various factors that encourage perpetrators to commit crimes. Human trafficking is a practice of modern slavery that degrades dignity and can threaten the survival of the general public. The target or targets of this trading practice are usually people who earn low income and have low education. It is important to know that this crime can be committed individually or collectively. It is said to be joint if it is carried out in the name of a business entity and in the interests of the corporation based on the work relationship and work environment of the corporation. Corporations as legal subjects for the criminal act of trafficking in persons are regulated in Article 13 of Law of the Republic of Indonesia Number 21 of 2007 concerning the Eradication of the Crime of Trafficking in Persons. The current obstacle is that the implementation or application of punitive sanctions against corporations is still not firm. This can be seen from the increasing number of cases where the perpetrator is a business entity or corporation. The method used in this research is a normative legal research method which examines legal materials such as books or articles that discuss human trafficking using secondary data for detailed analysis. qualitative. The aim of this research is to determine the factors that cause corporations to commit criminal acts of human trafficking in Indonesia and to find out how criminal sanctions are applied against corporations for criminal acts of human trafficking in Indonesia.